Application of the analytical hierarchy method in the area of defence expenditure managing - Dyachenko, Serhii; Artiushenko Оleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Optimisation of defence expenditures is critical for ensuring the combat capability of the military and maintaining national security. Ukraine is increasing its expenditure on armaments and military equipment, which requires efficient management of budgetary resources to achieve maximum impact. Effective management of budgetary resources is crucial not only for ensuring the combat capability of military formations, but also for maintaining national security. M e t h o d s . The article uses the AHP method with the use of pairwise comparisons and the Saaty scale to evaluate the criteria within the BOCR concept (benefits, costs, opportunities, risks). R e s u l t s . The article develops a decision-making model based on the AHP concept to help in the evaluation and selection of suppliers. The model evaluates suppliers using a set of criteria grouped into four categories: Benefits, Costs, Opportunities and Risks (BOCR). Each criterion, such as price, product quality, delivery time and supplier reliability, was assigned a weight using a pairwise comparison matrix based on the Saaty scale. The AHP approach allowed both quantitative and qualitative criteria to be integrated into the decision-making process. After evaluating the three suppliers, Supplier 1 was identified as the most suitable option with the highest BOCR of 1.033. C o n c l u s i o n s . The research conducted in this article has shown that the AHP-based decision-making model is an effective tool for optimising defence expenditure and improving procurement processes. Through the application of the BOCR concept, the model balances positive and negative factors, ensuring a transparent and efficient decision-making process. The use of pairwise comparisons ensures consistency of judgement and allows decision makers to rank alternatives in a systematic way. The paper emphasises the adaptability of the model to different operating environments: Microsoft Excel is used for data analysis and implementation, but programming languages can also be used. The results of the study demonstrate that multi-criteria optimisation methods such as AHP are valuable tools for optimisation in defence expenditure management, including the selection of suppliers of goods, works and services.